ChemInform Abstract: Efficient Synthesis of 9, 10‐Bis(phenylethynyl)anthracene Derivatives by Integration of Sonogashira Coupling and Double‐Elimination Reactions. Issue 30 (4th July 2013) - Toyota, Shinji; Mamiya, Daiki; Yoshida, Rie; Tanaka, Ryo; Iwanaga, Tetsuo; Orita, Akihiro; Otera, Junzo
Abstract Starting from aldehyde (I), a combination of Sonogashira coupling and double elimination with benzyl phenyl sulfones is used to synthesize unsymmetrical title compounds as fluorescent building blocks in material chemistry.